2021
DOI: 10.1111/jocd.14031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 0.15% isobutylamido thiazolyl resorcinol combined with hyaluronic acid vs 0.15% isobutylamido thiazolyl resorcinol or hyaluronic acid alone in melasma treatment: A randomized evaluator‐blind trial

Abstract: Melasma, an acquired chronic skin hypermelanosis, commonly manifests as symmetrical brown-gray patches on the face and may significantly affect the self-esteem and quality of life of patients. 1 The pathogenesis of melasma involves complex dynamic epidermaldermal interaction among various cell types, inflammation, oxidative stress, and photodamage. [2][3][4] All factors significantly contribute to its development. Melasma treatment is challenging and presents frequent relapses. Conventional treatments targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
(62 reference statements)
0
11
0
4
Order By: Relevance
“…Moreover, the addition of hyaluronic acid to Thiamidol seems to improve its bleaching effect in melasma. 27 Allergic contact dermatitis (ACD) is likely to occur during melasma treatment, as bleaching agents and sunscreens are potential sensitizers. ACD from sunscreen occurs in up to 0.8% of the population, 28 and hydroquinone is associated with ACD in 0.3% of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the addition of hyaluronic acid to Thiamidol seems to improve its bleaching effect in melasma. 27 Allergic contact dermatitis (ACD) is likely to occur during melasma treatment, as bleaching agents and sunscreens are potential sensitizers. ACD from sunscreen occurs in up to 0.8% of the population, 28 and hydroquinone is associated with ACD in 0.3% of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the superior performance of Thiamidol (43%) in our sample suggests the double‐layer application twice a day is a more efficient regimen for the bleaching of melasma. Moreover, the addition of hyaluronic acid to Thiamidol seems to improve its bleaching effect in melasma 27 …”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, we screened 813 records and reviewed the full texts of 488 studies (Figure 1). Ultimately, we included 36 studies, reported in 35 articles 42–76 . Detailed information about the study and participant characteristics, including the risk‐of‐bias evaluations and reasons for excluding studies is given in Appendix S3 and Appendix S4 (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We included one three‐armed RCT 51 with 30 participants per arm comparing the combination of ITR 0·15% and hyaluronic acid (HA) vs. ITR 0·15% and HA alone. With respect to MASI, the combination of ITR plus HA was superior to HA alone [MD –1·28 (95% CI –1·88 to –0·68); GRADE: ⨁⨁⨁◯] and ITR alone was superior to HA alone [MD –0·91 (95% CI –1·57 to –0·25); GRADE: ⨁⨁◯◯], whereas there was no significant difference between combination treatment and ITR alone [MD –0·37 (95% CI –1·13–0·39); GRADE: ⨁⨁◯◯].…”
Section: Resultsmentioning
confidence: 99%
“…The most recent entrant in the skin tone market is the imidazolyl derivative of resorcinol, thiamidol, identified through a high throughput screening of a large compound library on human tyrosinase protein. With an IC50 of 1 μM for tyrosinase enzyme inhibition, it is the most potent inhibitor known so far [129,168] The group has also demonstrated the efficacy of thiamidol on various hyperpigmentary conditions like melasma [189][190][191], solar lentigines [192], PIH [193], and UV-induced skin damage [194] and demonstrated its efficacy to be superior to HQ [190].…”
Section: Sds-induced Human Occluded Patch Test (A) Irritation Score I...mentioning
confidence: 99%